2009
DOI: 10.1016/j.jsv.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Super harmonic nonlinear lateral vibrations of a segmented driveline incorporating a tuned damper excited by non-constant velocity joints

Abstract: Chair of Advisory Committee: Dr. Alan Palazzolo Linear vibration measurement and analysis techniques have appeared to be sufficient with most vibration problems. This is partially due to the lack of proper identification of physical nonlinear dynamic responses. Therefore, as an example, a vehicle driveshaft exhibits a nonlinear super harmonic jump due to nonconstant velocity, NCV, joint excitation. Previously documented measurements or analytical predictions of vehicle driveshaft systems do not indicate nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Xu and Marangoni (1994a, 1994b) derived misalignment forces based on the kinematics of Hooke’s joint and concluded that the unbalance and misalignment excitation of Hooke’s joint produce first- and second-order vibration. Michael and Alan (Browne and Palazzolo, 2009) studied the phenomenon of nonlinear super harmonic jump due to the universal joint excitations on test bench. The secondary moment exciting the driveshaft system is derived with subsequent analysis showing the harmonic and super harmonic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Marangoni (1994a, 1994b) derived misalignment forces based on the kinematics of Hooke’s joint and concluded that the unbalance and misalignment excitation of Hooke’s joint produce first- and second-order vibration. Michael and Alan (Browne and Palazzolo, 2009) studied the phenomenon of nonlinear super harmonic jump due to the universal joint excitations on test bench. The secondary moment exciting the driveshaft system is derived with subsequent analysis showing the harmonic and super harmonic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling or universal joints are used to connect the shaft, which can compensate for installation errors. The super harmonic nonlinear lateral vibration effect caused by universal joints subject to misalignment was initially demonstrated by experiments [25,26]. The model and instability region of the universal joint has been presented and simulated, showing the correlation with physical test results [27,28].…”
Section: Introductionmentioning
confidence: 86%
“…These aspects of considering the automotive driveshafts as quasi-isometric (isometry with nonuniformity) CVJ (homokinetic) transmissions allows for the development of future research in torsional forced vibrations and the bending-shearing vibrations of automotive driveshafts. This starting point in the investigation of the geometric and kinematic isometric nonuniformities of driveshafts opens the door to modeling of the forced torsional dynamic behavior of the driveshafts in the region of nonlinear parametric vibrations as already mentioned in literature [9,[12][13][14] In Figure 14, the geometric nonuniformity isometry for the driveshaft…”
Section: Nonuniformity Of Geometric Vs Kinematic Isometry Of Drivesha...mentioning
confidence: 99%
“…What is very strange for this research paper is that it contains only two references: of which one is a self-citation in the same field of dynamic stability of shafts driven through a universal cardan joint. The experimental evidence on the nonuniformity of CVJ driveshaft transmissions is presented and high-lighted by Browne and Palazzolo in the paper [13]. But the most important experimental research on the nonuniformity of geometric and kinematic isometry of CVJ driveshafts was carried out by Steinwede during his PhD thesis [14] (pp.…”
Section: Introductionmentioning
confidence: 99%